Tindak Tutur Representatif dan Direktif pada Daftar Putar Belajar Jadi MC dalam Kanal Youtube Maya Rachma (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2026)
Pragmatics not only highlights language structure, but also the speaker's purpose and intention in a communication event. This study on representative and directive speech acts in the “Belajar Jadi MC” playlist on Maya Rachma's YouTube channel is important because social media, especially YouTube, has developed into an influential public space that shapes people's perspectives. This scientific article uses a theoretical approach in the form of a pragmatic approach and a methodological approach, namely a qualitative descriptive approach.  The techniques used by the researcher were the Simak Bebas Libat Cakap (SBLC) technique and the note-taking technique. These two techniques were used because the author did not interact directly but only listened and took notes from existing data. The results of the study found 8 types of representative speech acts and 4 types of directive speech acts. There were 65 representative speech acts, including 9 informative speech acts, 12 suggestive speech acts, 13 mentioning speech acts, 9 stating speech acts, 6 exemplifying speech acts, 9 explaining speech acts, 4 showing speech acts, and 3 speculating speech acts. Meanwhile, there were 33 instances of directive speech acts, including 9 requests, 7 invitations, 8 commands, and 9 orders. The author hopes that this research can be used as a reference for further studies on representative and directive speech acts and increase knowledge and insight in the field of pragmatics, especially in the study of representative and directive speech acts.